2000
DOI: 10.2306/scienceasia1513-1874.2000.26.207
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Multiple shoots of mulberry (Morus alba cv Khonpai), a NaCl-tolerant cultivar, were grown on MS media without or with NaCl. On medium with increasing NaCl concentration up to 150 mM, the shoots exhibited slightly reduction in growth. On the other hand, when the concentration of NaCl increased to 200 mM, the growth was completely inhibited and the necrosis of leaves tissue was observed. The relative water content was significantly decreased in leaves treated with NaCl concentration of 150 and 200 mM compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The increase in hydrogen peroxide concentration in response to salt stress was observed with other plant species, e.g., mung bean (Vigna radiata), rice (Oryza sativa), and mulberry (Morus sp.) [54,60,61]. The results of our study indicated a positive correlation between the level of hydrogen peroxide in roots, stems and leaves of B. vulgaris and NaCl concentration.…”
Section: Effect Of Salinity On the Growth And Biochemical Parameters Of B Vulgarissupporting
confidence: 61%
See 1 more Smart Citation
“…The increase in hydrogen peroxide concentration in response to salt stress was observed with other plant species, e.g., mung bean (Vigna radiata), rice (Oryza sativa), and mulberry (Morus sp.) [54,60,61]. The results of our study indicated a positive correlation between the level of hydrogen peroxide in roots, stems and leaves of B. vulgaris and NaCl concentration.…”
Section: Effect Of Salinity On the Growth And Biochemical Parameters Of B Vulgarissupporting
confidence: 61%
“…The accumulation of compatible solutes, including proline, is a very important defense mechanism against salinity stress and is responsible for intracellular osmotic equilibrium maintaining [52,53]. An increase in proline levels in plants growing under salt stress was observed in different plant species, including canola (Brassica napus), dill (Anethum graveolens), mulberry (Morus alba cv Khonpai), pistachio (Pistacia vera L.) and Jerusalem artichoke (Helianthus tuberosus) [28,39,[54][55][56][57]. The accumulation of proline in plants growing under salt stress is associated with the low activity of antioxidant enzymes [58], which is accompanied by an increase in the level of ROS [21,59].…”
Section: Effect Of Salinity On the Growth And Biochemical Parameters Of B Vulgarismentioning
confidence: 99%
“…However, high chlorophyll content (SPAD value) was detected in salt-tolerant genotypes. These higher chlorophyll values can be ascribed to an improved photosynthetic rate and higher dry matter production [31,32]. The reduction in chlorophyll content under marginal environments has been observed in many previous studies [19,25,31].…”
Section: Plant Height Number Of Tillers and Chlorophyll Spad Valuementioning
confidence: 82%
“…Many functions have been postulated for proline accumulation in plant tissues, proline and free amino acids could be involved in the osmotic adjustment of plants [45] and could also be a protective agent of enzymes and membranes [46]. When plant subjected to drought stress, plants maintain their water content by accumulation of compatible organic solutes act as osmoprotectants, such as proline, in their cytoplasm [47]. Proline accumulation under drought stress has been reported and suggested to be a biochemical marker for increased stress tolerance in plant species under stress conditions.…”
Section: Proline Total Amino Acids and Total Proteinmentioning
confidence: 99%